(untitled) (Research, Society and Development, 2021)
Due to its position of vulnerability in the body, the face is an anatomical region with a high incidence of physical aggression and accidents. According to the World Health Organization (WHO), trauma is among the main causes of death and disability in the world, together with the alarming growth of all forms of violence in our society today, especially interpersonal physical aggression. Although this type of crime for the most part does not result in death, they are responsible for significant sequelae. This work is an integrative review, aiming to analyze studies on the epidemiological profile of oral and maxillofacial trauma in victims of physical aggression. The articles compiled in this study were selected using the following databases: PubMed, Lilacs and Scielo. The survey included all the publications found, according to the aforementioned databases, without a time frame until 2020. Finally, no language restriction was applied, using the standardized descriptors: Aggression; Maxillofacial Lesions; Epidemiology and its English counterparts. After analyzing the works, it was observed that victims of physical aggression indicated a predominance of males, the incidence of aggression prevailed between the second and third decade of life, at night, over recurrent bone fractures in physical aggression, the highlight is for the nasal anatomical complex, mandibular region and the zygomatic-maxillary complex, markedly in the middle third of the face. Finally, it is evident the need for a fruitful attention to these data that can benefit society by supporting preventive government strategies to control the events that can result in trauma of this etiology.